When will Black children be well? Interrupting anti-Black violence in early childhood classrooms and schools. (September 2021) - Boutte, Gloria; Bryan, Nathaniel
We demonstrate that Black children are not faring well in early childhood settings and suggest ways educators can work toward ensuring that Black children thrive and flourish in schools. Five types of daily violence/traumas that Black children experience in schools are described against the ethical backdrop First Do No Harm (Boutte, 2008). Evoking the Maasai legend that asks, How are the children? we share two examples of Black males' school experiences, though we readily acknowledge that Black females experience parallel issues. We present an overview of five types of school violence (physical, symbolic, linguistic, curricular/pedagogical, and systemic), and conclude by offering ways to interrupt these to ensure that Black children are well.